Proximate Composition and Bioactive Compounds of Cocoa Bean Shells as a By-Product from Cocoa Industries in Indonesia - Mohamad Djali; Kimberly Santasa; Rossi Indiarto; Edy Subroto; Fetriyuna Fetriyuna; Elazmanawati Lembong (Foods, 2023)
Cocoa bean shell (CBS) is a by-product from cocoa processing which is abundant in Indonesia, one of the largest cocoa-producing countries. It has a great potential for being processed into food ingredients due to its comparable composition to cocoa nibs. The present study was conducted to identify the proximate composition and bioactive compounds in CBS produced at several cocoa industries in Indonesia utilizing different cocoa varieties (Criollo and Forastero) and processing techniques (fermented, non-fermented, pulp washing, and drying), which remain unknown. The results showed that the CBS derived from roasted Criollo cocoa pods in the Kendeng Lembu cocoa industry had ash and protein content of about 8.21% and 18.79%, respectively, which was higher than other industries. Additionally, the concentration of bioactive substances was higher here than it was elsewhere. This included total phenolic (136.2 mg GAE g−1) and theobromine (22.50 mg g−1). The lowest ash and protein concentration found in CBS was from Forastero cocoa pods, non-fermented like Sulawesi cocoa. These values were 6.48% and 15.70%, respectively. The concentration of theobromine (15.40 mg g−1) was also lower compared to other industries.